MODELLING FRUIT AND VEGETABLE CONSUMPTION IN SERBIA - Ubiparip Samek, Dragana; Pezo, Lato; Mastilović, Jasna; Kovač, Renata; Zoranović, Tihomir; Vlahović, Branislav (Food and Feed Research, 2022)
Although regular intake of fruits and vegetables has an essential role in a healthy diet and well-being, a majority of consumers in Serbia have a suboptimal intake of these groceries. To understand the main determinants of this unsatisfactory situation, the study tested an extended model of the theory of planned behavior intending to suggest necessary steps for improving fruits and vegetables daily intake. This theory, extended for the role of knowledge, was tested using structural equation modeling. Fit indices confirmed the utility of this extended model of the theory of planned behavior in explaining consumers’ behavior as well as the mediating role of behavioral intentions. Serbia, as one of the central developing countries in the Balkans, was chosen to test the model with the possibility of applying it to other developing countries facing malnutrition. Data were collected in north Serbia, through an online survey (n=688). Despite consumers’ high awareness of fruits and vegetables' beneficial health effects, the influence of consumers’ knowledge only is not sufficient to trigger behavioral changes. Consumers’ intentions and behavior should be influenced indirectly, by changing their attitudes and subjective norms. All custom-made activities promoting a higher fruit and vegetable intake should consider the present findings to achieve a bigger effect on behavioral changes among consumers.
Keywords: consumer behavior; fruit consumption; structural equation modeling; theory of planned behavior; vegetable consumption